Dengue Virus Serotype 2 and Its Non-Structural Proteins 2A and 2B Activate NLRP3 Inflammasome - Shrivastava, Gaurav; Visoso-Carvajal, Giovani; Garcia-Cordero, Julio; Leon-Juarez, Moisés; Chavez-Munguia, Bibiana; Lopez, Tomas; Nava, Porfirio; Villegas-Sepulveda, Nicolás; Cedillo-Barron, Leticia (Frontiers in Immunology, 2020)
Dengue is the most prevalent and rapidly transmitted mosquito-borne viral disease of humans. One of the fundamental innate immune responses to viral infections includes the processing and release of pro-inflammatory cytokines such as interleukin (IL-1β and IL-18) through the activation of inflammasome. Dengue virus stimulates the Nod-like receptor (NLRP3-specific inflammasome), however, the specific mechanism(s) by which dengue virus activates the NLRP3 inflammasome is unknown. In this study, we investigated the activation of the NLRP3 inflammasome in endothelial cells (HMEC-1) following dengue virus infection. Our results showed that dengue infection as well as the NS2A and NS2B protein expression increase the NLRP3 inflammasome activation, and further apoptosis-associated speck-like protein containing caspase recruitment domain (ASC) oligomerization, and IL-1β secretion through caspase-1 activation. Specifically, we have demonstrated that NS2A and NS2B, two proteins of dengue virus that behave as putative viroporins, were sufficient to stimulate the NLRP3 inflammasome complex in lipopolysaccharide (LPS)-primed endothelial cells. In summary, our observations provide insight into the dengue-induced inflammatory response mechanism and highlight the importance of DENV-2 NS2A and NS2B proteins in activation of the NLRP3 inflammasome during dengue virus infection.